The Effect of Supportive Group Therapy Toward DM Patients Depression - Ida Nur Imamah; Norman Wijaya Gati (Gaster, 2022)
Diabetes mellitus is one of the global health problems which can leads complications, include kidney failure, blindness, stroke and amputation of body parts. Problems and complications that arise in DM can lead to depression. Depression arises because it is influenced by many psychological factors, both directly and indirectly. Supportive group therapy is therapy that is openly used to express thoughts and emotions. Supportive group therapy conduct patient to exchange of experiences. This experiences are expected to change the behavior of DM patients through imitation or reinforcement provided by the patient's environment. The purpose of this study was to determine the effect of group activity therapy towars DM patients depression. This research is an experimental study without Â control group in the Padi Mas group in Surakata. This study uses a questionnaire using the Beck Depression Inventory (BDI). The research method uses univariate and bivariate analysis using the chi square test. The results showed that after group therapy there was a change in the depression condition but it was not significant, most of them still had moderate signs and symptoms of depression.